Time-resolved photoelectron diffraction imaging of methanol photodissociation involving molecular hydrogen ejection - Yoshikawa, Kazuki; Kanno, Manabu; Xue, Hao; Kishimoto, Naoki; Goto, Soki; Ota, Fukiko; Tamura, Yoshiaki; Trinter, Florian; Fehre, Kilian; Kaiser, Leon; Stindl, Jonathan; Tsitsonis, Dimitrios; et al. (ROYAL SOCIETY OF CHEMISTRY, 2025)
Imaging ultrafast atomic and molecular hydrogen motion with femtosecond time resolution is a challenge for ultrafast spectroscopy due to the low mass and small scattering cross section of the moving neutral hydrogen atoms and molecules. Here, we propose time- and momentum-resolved photoelectron diffraction (TMR-PED) as a way to overcome limitations of existing methodologies and illustrate its performance using a prototype molecular dissociation process involving the sequential ejection of a neutral hydrogen molecule and a proton from the methanol dication. By combining state-of-the-art molecular dynamics and electron-scattering methods, we show that TMR-PED allows for direct imaging of hydrogen atoms in action. More specifically, the fingerprint of hydrogen dynamics reflects the time evolution of polarization-averaged molecular-frame photoelectron angular distributions (PA-MFPADs) as would be recorded in X-ray pump/X-ray probe experiments with few-femtosecond resolution. We present the results of two precursor experiments that support the feasibility of this approach.We explore time- and momentum-resolved photoelectron diffraction imaging (TMR-PED) to visualize hydrogen dynamics during methanol dication dissociation. Our approach allows real-time tracking of hydrogen migration and molecular fragmentation.